Zentangle. 9 color with mixed media - McNeill, Suzanne (Fox Chapel Publishing, 2014)
Inside you'll find 31 all-new tangles with inspiring ideas for adding expressive color to your Zentangle art. Easy and beautiful techniques for combining cool colors with mixed media.